HYPERVITAMINOSIS B12 – IS IT A SIGNIFICANT PARAMETER IN THE CONTEXT OF CANCER? – REVIEW PAPER - Emilia Majewska; Izabela Domańska; Aleksandra Sagan; Monika Domagała; Joanna Wiewióra; Weronika Duda; Małgorzata Piśkiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective Vitamin B12 plays an important role in hematopoiesis, the synthesis of myelin sheaths and the DNA methylation process. Food products rich in vitamin B12 include meat, offal, eggs, fish, and fermented plants. Hypervitaminosis B12 is serum level of this vitamin exceeding the reference range. Causes of this condition include liver or kidney failure, autoimmune diseases, infections, excessive supplementation, improper diet and malignant neoplasms. Materials and Methods The aim of our paper is analyzing studies about relationship between hypervitaminosis B12 and cancer disease. All articles are available in Google Scholar database in English, full-text online and free of charge. The phrase used for the search was ‘Vitamin B12 cancer’. Results Conclusions drawn by analyzed studies. Oncologic patients exhibit higher average levels of vitamin B12. Hypervitaminosis B12 adversely impacts survival time in patients with diagnosed cancer. Prolonged hypervitaminosis is more frequently associated with the future occurrence of malignant neoplasms compared to temporarily elevated levels. During cancer regression, vitamin B12 levels normalize. Increased mortality among patients with hypervitaminosis B12 is observed both in oncologic and internal medicine patients. Conclusions The diagnosis of hypervitaminosis B12 should not be marginalized. Detailed diagnostics should be implemented to find its cause. In the future, monitoring the level of vitamin B12 may prove helpful in cancer prevention and in assessing the effectiveness of anticancer treatment. The detailed connections between vitamin B12 and the occurrence of malignant tumors are still unclear and require further scientific research.